Memory landscapes and stories of shame: the coexistence of Greece, Cyprus and Turkey as an affective “Mission Impossible” - Karaiskou, Vicky (Interdisciplinary applications of shame/violence theory, 2022)
The chapter focuses on Greece, Cyprus and Turkey and discusses how affective narratives in public space create “memory landscapes” that determine perceptions of historical past and regulate attitudes in the present time. Since the nineteenth century, reiterations of visual and verbal narratives on loss in public discourse among the three countries function as a “trauma-drama”. They nourish victimisation, ensure accumulation of anger, fear and sadness for the injustice done, as well as kindle vicious circles of duty (and shame) with regard to the perished. We use two events as case studies to explore how “figures of memory” and their deriving visuality produce powerful affective narratives and “regimes of truth” that activate the collective psyche triggering multilevel reactions in the social and political sphere. The first event is the staging of two ancient dramas at the ancient theatre of Salamis in Cyprus, in 2015 and 2016. The second is the change of status of Hagia Sophia, the Byzantine cathedral in Istanbul, from a museum to a fully fledged mosque, in 2020. The chapter proposes that awareness of the power visuality exercises and critical revising of the master narratives can shift attention into the building of a future based on mutual understanding.